The Impact of the Public Distribution System in India. Issue 3 (December 2016) - Thampi, Anjana
In the context of the recent evidence of a revival of the PDS in certain states, its impact between 2004–2005 and 2011–2012 on the nutritional indicators of children aged 7–19 years was studied by state. This exercise showed that the PDS has had a significant impact on the longer-term nutritional indicator in three of the four functioning states and on the short-term indicator in two reviving states. This indicates that the revival has begun to translate into nutritional gains and catch-up growth of children in some states. Two sets of indicators were used to understand the mechanisms through which these gains were attained. One considered the dependence on the calories provided by PDS commodities; this showed a high dependence on PDS for sufficient intake of calories in functioning states and increasing dependence in certain reviving states. The second indicator was an index of dietary variety. This followed a pattern of higher dietary diversity in beneficiary households in most of the functioning and reviving states. These are encouraging results which offer scope for further reforms.